Pemanfaatan Pepaya Sebagai Selai dalam Rangka Peningkatan Pendapatan Masyarakat Desa Helumo - Nilawaty Yusuf (BADAN PENERBIT STIEPARI PRESS, 2023)
There is a market opportunity to develop papaya fruit to be produced into products of economic value. This community service is carried out with the aim of increasing the knowledge and skills of the community, especially housewives in Helumo Village, Suwawa District, Bone Bolango Regency in utilizing papaya fruit as a processed jam product. The counseling and training methods for making papaya into jam are used by the Service Team. The results of the service show that housewives who are trained can make papaya into processed jam as an alternative product solution that can be produced to increase family income.